Desain Cover Buku dengan Teknik Overlap Menggunakan Canva - selina, Natria; Dini, Juan (Cosmic Jurnal Teknik, 2024)
This research investigates the potential of overlap techniques in book cover design using the online graphic design platform, Canva. The focus of this research lies in exploring the visual and aesthetic creativity that can be produced through the use of overlap techniques. Book covers are an important element in attracting readers' attention and reflecting the contents of the book. The overlap technique, with the use of overlapping visual elements, can be an effective strategy for creating attractive and informative cover designs. This research aims to explore the potential of overlap techniques in book cover design using the Canva platform. This research uses qualitative methods with case studies on fiction and non-fiction book cover designs. Data was collected through analysis of existing cover designs and interviews with graphic designers. The research results show that the overlap technique can produce attractive and informative cover designs. This technique allows designers to display various visual elements that are relevant to the book's content, creating dynamic and eye-catching compositions. This research also found that using the Canva platform can help designers, even without in-depth graphic design skills, to produce professional and attractive cover designs using the overlapping technique. Book cover design is also a critical aspect that can attract the attention of potential readers and reflect the essence of the book's contents. The overlapping technique in book cover designs using Canva can give an interesting and dynamic visual impression. By utilizing Canva's special features, book cover designs can be produced easily and effectively. Keywords: book cover design, overlap technique, Canva, graphic design, visual communication